Is cabergoline mystical in euprolactemic polycystic ovarian syndrome - Taiseen, Gazala; Vellanki, Janaki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Polycystic ovarian syndrome (PCOS) is most common in reproductive age females. Cabergoline is a potent long-acting dopamine agonist play an important role in decreasing high prolactin secretion which is present in 30–40% of PCOS and induce ovulation in those with normal prolactin level also. This is attributed to reduction of an occult hyperprolactinemia in PCOS patients. Methods: This is a randomized, prospective, controlled study includes 100 Euprolactinemic infertile PCOS, 50 in each group, Group A (letrozole cabergoline group) patients received tablet letrozole 5 mg/day in 2 divided doses 2.5 mg from cycle day 3 to day 7 plus cabergoline tablet 0.25 mg, half tablet twice weekly for 4 weeks starting from cycle day 3 with letrozole despite normal serum prolactin level. Group B (letrozole Group):patients received only letrozole same as group A. Primary outcomes-ovulation rate, number of dominant follicles and secondary outcomes-pregnancy, miscarriage, multiple pregnancies, OHSS, side-effects of cabergoline were studied. Statistical analysis was done. Results: Study groups compared for the demographic characters, basic clinical data, duration and type of infertility which showed no significant difference. Statistically significant difference in group A ovulation rate 76% (p value 0.0124), number of dominant follicles (p value 0.029). Pregnancy rate 72% in group A and 48% in group B (p value 0.014). No statistical difference in miscarriage (p value 0.15), twin pregnancies (p value 0.86), OHSS (p value 1.0) and no side effects. Conclusions: Addition of cabergoline to Letrozole in induction of ovulation in euprolactinemic infertile PCOS results in increased ovulation, high pregnancy rate compared to use of letrozole alone, with very few side-effects.